Perencanaan dan Perancangan Ruang Pamer dan Pusat Produksi Patung dan Ukiran di Desa Singapadu Kaler, Gianyar, Bali - I Kadek Surya Cipta; I Wayan Runa; Ni Wayan Nurwarsih (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Indonesia is a country that is rich in artistic diversity, one of which is sculpture. Bali is one of the islands that has a lot of arts and culture, one of which is Singapadu Kaler Village which has a characteristic in the form of sculptures made from solid stone. The people of Singapadu Kaler Village work as craftsmen and sellers of statues, based on population data with a total of 1,324 people with jobs as sculptors or sculpture and carving craftsmen as many as 662 people, so 50% of the people in the Singapadu Kaler area. An important problem is also owned by the sculptor community, currently the sculpture craft of Singapadu Kaler Village has decreased in terms of sales or tourist arrivals to Singapadu Kaler. This problem is caused by the fact that the sculptures do not yet have facilities that can display their handicrafts. The design approach method uses an economic approach, with the design approach being carried out, it is expected to be able to fulfill the function, space requirements and aesthetics in the overall architectural appearance. Therefore, the Center for Sculpture and Carving Crafts is proposed with the basic concept of Fun, Dynamic and Creative Industries. The theme used is KontemporerArchitecture where the use of Contemporary Architecture aims to create an attractive building as well as become an icon in Singapadu Kaler.